2019
DOI: 10.1039/c9sm00262f
|View full text |Cite
|
Sign up to set email alerts
|

Physics-based prediction of biopolymer degradation

Abstract: A continuum model elucidates the complex degradation kinetics of insoluble biomatter by bacterial communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In this model, the bio-chemo-mechanically coupled kinetics of polymer degradation are assessed. The model includes parameters of the solvent, polymer characteristics, enzyme secretion and diffusion, kinetic parameters, and parameters to describe degradation that are estimated during the modelling process [ 218 ]. Another model describing biodegradation proposes a generalized constitutive model for municipal solid waste.…”
Section: Sustainability Biodegradation and Recyclingmentioning
confidence: 99%
“…In this model, the bio-chemo-mechanically coupled kinetics of polymer degradation are assessed. The model includes parameters of the solvent, polymer characteristics, enzyme secretion and diffusion, kinetic parameters, and parameters to describe degradation that are estimated during the modelling process [ 218 ]. Another model describing biodegradation proposes a generalized constitutive model for municipal solid waste.…”
Section: Sustainability Biodegradation and Recyclingmentioning
confidence: 99%
“…Abi-Akl et al recently described the crux of the challenge inherent to lifetime modeling, in that conventional scaling arguments are insufficient due to the mutually inclusive effects of physical and biochemical processes. They developed a theoretical model that accounts for the biochemo-mechanically coupled kinetics of polymer degradation.…”
Section: Barriers/research Needsmentioning
confidence: 99%
“…Pockets of knowledge from degradation chemistry, drug delivery, and enzyme chemistry should be rendered by using the broader framework of structure−property relations to relate macromolecular and chemical changes to engineering properties. 71 Abi-Akl et al 110 recently described the crux of the challenge inherent to lifetime modeling, in that conventional scaling arguments are insufficient due to the mutually inclusive effects of physical and biochemical processes. They developed a theoretical model that accounts for the biochemo-mechanically coupled kinetics of polymer degradation.…”
Section: Alternative Feedstockmentioning
confidence: 99%
“…Abi‐Akl et al. [ 180 ] have developed a theoretical model biochemo‐mechanically coupled kinetics of polymer degradation. The authors have revealed the capability of biodegraders to dissociate the external boundary and to penetrate it to degrade its internal mechanical properties.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%